Rosemary Essential Oil-Loaded Lipid Nanoparticles: In Vivo Topical Activity from Gel Vehicles - Lucia Montenegro; Lorella Pasquinucci; Agata Zappalà; Santina Chiechio; Rita Turnaturi; Carmela Parenti (MDPI AG, 2017)
Although rosemary essential oil (EO) shows many biological activities, its topical benefits have not been clearly demonstrated. In this work, we assessed the effects on skin hydration and elasticity of rosemary EO after topical application via gel vehicles in human volunteers. To improve its topical efficacy, rosemary EO was loaded into lipid nanoparticles (NLCs) consisting of cetyl palmitate as a solid lipid, and non-ionic surfactants. Such NLCs were prepared using different ratios of EO/solid lipid and those containing EO 3% w/w and cetyl pamitate 7% w/w were selected for in vivo studies, showing the best technological properties (small particle size, low polydispersity index and good stability). Gels containing free EO or EO-loaded NLCs were applied on the hand skin surface of ten healthy volunteers twice a day for one week. Skin hydration and elasticity changes were recorded using the instrument Soft Plus. Gels containing EO-loaded NLCs showed a significant increase in skin hydration in comparison with gels containing free EO. Skin elasticity increased, as well, although to a lesser extent. The results of this study point out the usefulness of rosemary EO-loaded NLCs for the treatment of cutaneous alterations involving loss of skin hydration and elasticity.